2010
DOI: 10.4250/jcu.2010.18.4.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Statins on the Epicardial Fat Thickness in Patients with Coronary Artery Stenosis Underwent Percutaneous Coronary Intervention: Comparison of Atorvastatin with Simvastatin/Ezetimibe

Abstract: BackgroundEpicardial fat is a visceral thoracic fat and known to be related with presence of dyslipidemia and coronary arterial stenosis. We evaluated the effects and differences of statins on epicardial fat thickness (EFT) in patients underwent successful percutaneous coronary intervention (PCI).MethodsIn this retrospective cohort study, we enrolled consecutive patients underwent successful PCI and scheduled six to eight-months follow-up coronary angiography from March 2007 to June 2009. EFT was measured by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 26 publications
(28 reference statements)
2
54
0
1
Order By: Relevance
“…The effect on EAT by medications has been also evaluated. Park et al [73] reported a significant decrease in EAT thickness in patients treated with atorvastatin, whereas it increased during pioglitazone treatment [74].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…The effect on EAT by medications has been also evaluated. Park et al [73] reported a significant decrease in EAT thickness in patients treated with atorvastatin, whereas it increased during pioglitazone treatment [74].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…In a 2-year study of 145 patients with coronary artery stenosis, statins were shown to improve lipid profiles and also significantly decrease epicardial fat thickness. 40 Another study performed in type 2 diabetes patients showed that insulin replacement therapy resulted in a reduction of epicardial fat thickness. 41 It is still unknown whether the decrease of epicardial fat volume following weight loss or pharmaceutical treatment is associated with changes in the inflammatory state of epicardial fat.…”
Section: Conclusion: Therapeutic Implications and Future Directionsmentioning
confidence: 99%
“…The results of other large studies have revealed that the degree of coronary calcification correlates with the amount of pericardial fat, and that this correlation predicts progression of atherosclerosis in subjects with low calcification followed from the outset 7 . Increased number of macrophages, T-lymphocytes and mast cells in epicardial fat but not in SAT have been demonstrated in patients with coronary artery disease by several researchers independently 8,9 and regression of epicardial fat has been observed in relation to weight reduction 10 , exercise 11 or following administration of either atorvastatin 12 or ezetimibe 13 . Whether this reduction leads to a decreased cardiovascular risk remains unclear and needs to be further examined.…”
Section: Fat Depots: Perivascular Epicardial Visceral and Subcutaneousmentioning
confidence: 99%